Amide- and urea-based synthetic anticonvulsants, antihypoxics, and inducers of the hepatic monooxygenase system; VII; Effect of benzhydrylureas on the cytochrome P-450-dependent liver monooxygenase system; Pharmaceutical Chemistry Journal; Vol. 27, iss. 6 - Bakibaev A. A. Abdigali Abdimanapovich; Akhmedzhanov R. R. Rafik Raviljevich; Novozheeva T. P.; Filimonov V. D. Viktor Dmitrievich; Tignibidina А. S.; Saratikov А. S.; Shtrykova V. V. Viktoriya Viktorovna (1993, 1993)
Title screen